Asserting the Nation: The Dominance of National Narratives in Policy Influencers' Constructions of Higher Education Students. (June 2020) - Brooks, Rachel
Drawing on interviews with 26 higher education 'policy influencers' from six European countries (Denmark, England, Germany, Ireland, Poland, and Spain), this article considers the ways in which students were commonly understood by this particular group of social actors. It argues that, although a number of the characteristics of contemporary students identified by the interviewees are evident across many nation-states within Europe, they were frequently discussed and explained in terms of very distinct 'national narratives', with policy influencers often making reference to their country's specific history and culture. The implications of such narratives for European higher education and geopolitical relations more generally are explored.